The influence mechanism of job satisfaction among Chinese rural teachers—a conservation of resources perspective - Yu, Hui; Gao, Xiaona; Yu, Zhi (Frontiers in Psychology, 2025)
Rural teachers are a cornerstone of China’s education system, entrusted with the critical mission of disseminating knowledge, fostering intellectual growth, and shaping the future in remote areas. However, their job satisfaction is influenced by a complex array of factors, which this study investigates through the theoretical lens of Conservation of Resources (COR) Theory. This study employed a cross-sectional design and analyzed data collected from 1,038 rural teachers in China. A multiple linear regression analysis was conducted to examine how variations in key resource domains impact their job satisfaction. The regression analysis revealed that perceived deficits in several resource areas significantly predicted lower job satisfaction. Specifically, we found that reductions in mental health resources, development and security resources, welfare-and-treatment resources, and interest-efficacy resources were all significantly associated with decreased satisfaction. Among these, a lack of interest-efficacy resources demonstrated the strongest negative association. The findings strongly support the application of COR Theory in this context, indicating that the loss of key personal and professional resources is a critical determinant of job satisfaction among rural teachers. We conclude that interventions aimed at enhancing job satisfaction should be structured around five core dimensions: fostering career interest and self-efficacy, ensuring professional development and security, promoting work–life harmony, improving the salary and welfare system, and safeguarding psychological health.